Unveiling the past : a novel - Sawyer, Kim Vogel (WaterBrook Press, 2020)
"Newlyweds and cold case detectives Sean and Meghan Eagle have been given the task of investigating the twenty-years-past disappearance of a husband and father, Anson Menke. A judge ruled that the missing man chose to leave the country and abandon his family, but his wife wouldn't concede that he left his family nor declare him dead. Their mother now gone, his children want answers"--